Comparison of small group-based education with maternal participation and routine education on adolescent girls' menstrual health behaviors, a clinical trial Reihaneh - Reihaneh Jarrahi; Nahid Golmakani; Seyyed Reza Mazlom (Tehran University of Medical Sciences, 2020)
Background & Aim: Menstrual health is an important aspect of adolescent health. Most girls do not have proper information about menstrual health, and incorrect information from unreliable sources makes problems for them. Aim of this study was to compare small group-based education with maternal participation and routine education on adolescent girls' menstrual health behaviors. Methods & Materials: This randomized clinical trial study was performed on 60 high school students with regular menstruation in the groups of intervention and control. Among high schools in Mashhad in 2018, two schools were assigned to one of two groups by lottery. Menstrual health education was provided to the intervention group in four sessions as the groups of 3-4 people. For mothers in this group, two 2-hour sessions with the same content were held and the students in control group received routine education. Data were collected by a questionnaire on menstrual health behaviors, before the intervention, after the end of the first and second menstrual cycle. Data were analyzed by Mann-Whitney, Chi square and independent samples t-test using the SPSS software version 16. Results: before the intervention, there was a statistically significant difference in the menstrual health behaviors score (P=0.199). After the intervention, mean score of menstrual health behaviors (the end of the first and second menstrual cycles) significantly increased (P<0.001) for the two groups. Also, mean score of menstrual health behaviors for the intervention group was significantly higher than that of for the control group (P<0.001). Conclusion: The small group-based education with the participation of mothers in comparison to routine education was more effective in promoting menstrual health behaviors in adolescent girls. This method is recommended to health planners for education of health issues, including menstrual health. Clinical trial registry: IRCT20180904040952N2